(untitled) (People’s Journal of Management, 2023)
This paper aims to analyze the relationship between transformational leadership variables and employees’ job satisfaction in the educational sector of Nepal. Transformational leadership is grounded in moral foundations that are based on four components: Idealized influence, Inspirational motivation, Intellectual stimulation and Individualized consideration. The research uses Multifactor Leadership Questionnaire (MLQ form 5X) for measuring Transformational leadership style whereas Minnesota Satisfaction Questionnaire (MSQ) is used to measure the level of job satisfaction among 200 teachers and faculties from educational institutions. The study investigates transformational leadership and job satisfaction by means of descriptive and analytical research methodology. Transformational leadership behavior must be considered by the educational leaders to insure the employees’ job satisfaction which leads to increment of effectiveness, efficiency and performance of the employees.